Transformation of Value and Character Education for Mentally Healthy Adolescents in the Digital Era through Islamic Education - syarniah, syarniah; Fidzi, Ridhahani; Hamdan, Hamdan; Ma'ruf, Hidayat; Rachmadi, Agus (JURNAL CITRA KEPERAWATAN, 2025)
Adolescents are individuals in a period of growth and development that is synonymous with finding and building identity towards maturity. Adolescent behavior is very easily influenced by the surrounding environment. The current digital era makes the flow of communication, information, and individual freedom unlimited. Islamic education is needed to shape the behavior and character of adolescents who have akhlakul karimah and healthy soul. The purpose of this study is to analyze the transformation of character education and adolescent values towards mental health in the digital era through Islamic education. This research method is qualitative with a library research approach. Data sources come from literature reviews from research journals, books and other scientific articles according to the theme. Data is collected through literature study and analyzed by analyzing Islamic education in the process of transforming character and value education for adolescents in the digital era towards a healthy soul. The main focus of the research is to describe the transformation of character and value education in mentally healthy adolescents in the digital era through Islamic education. The accuracy of the results of this research analysis was carried out by triangulating the data analysis results involving experts according to expertise. The results of this research analysis show that Islamic education based on the Qur'an, Sunnah/Hadith, and Ijtihad is very appropriate for transforming value and character education which is also in line with mentally healthy values, especially for adolescents in the digital era.